IMPROVING STUDENTS’ WRITING SKILL ON RECOUNT TEXT THROUGH WORDLESS PICTURE BOOK - Lestari, Fuji; Apriliaswati, Rahayu; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted based on the problems found from observation on teaching and learning process. This research aimed to investigate how Wordless Picture Book improved students’ writing skill on recount text to the eight grade students of SMPN 1 Sungai Ambawang in academic year 2017/2018. This research was conducted by using Classroom Action Research and the subject was the eighth grade students in class VIII D. In collecting the data, the writer used observation checklist table, field note and writing test. The result showed that students’ problems in writing recount text such as organization of the text, using simple past tense and students’ interest in writing recount text had been solved by using Wordless Picture Book as the teaching medium. The students’ ability to organize the text improved through the chronological pictures, students’ ability in using simple past tense improved through events within pictures and students’ interest in writing recount text improved through cartoon pictures within Wordless Picture Book. It can be concluded that Wordless Picture Book can be used as a medium to improve students’ writing skill on recount text such as organization of the text, using simple past tense sentence and students’ interest in learning writing recount text. Keywords: Wordless Picture Book, Recount Text, Writing Skill.